Differences in global gene expression in peripheral blood mononuclear cells indicate a significant role of the innate responses in progression of dengue fever but not dengue hemorrhagic fever - Sukathida Ubol (2018)
Background. Dengue virus infection causes an array of symptoms ranging from dengue fever (DF) to dengue hemorrhagic fever (DHF). The pathophysiological processes behind these 2 clinical manifestations are unclear. Methods. In the present study, genomewide transcriptomes of peripheral blood mononuclear cells (PBMCs) collected from children with acute-phase DF (i.e., DF PBMCs) or acute-phase DHF (i.e., DHF PBMCs) were compared using microarray analysis. Results of genome screening were validated at the genomic and proteomics levels. Results. DHF had stronger influences on the gene expression profile than did DF. Of the affected genes, metabolic gene expression was influenced the most. For the immune response category, 17 genes were more strongly upregulated in DF PBMCs than in DHF PBMCs. Eight of the these 17 genes were categorized as belonging to the interferon (IFN) system. The up-regulation of IFN-related genes was accompanied by strong expression of CD59, a complement inhibitor. DHF PBMCs expressed genes involved in T and B cell activation, cytokine production, complement activation, and T cell apoptosis more strongly than did DF PBMCs. Conclusion. We hypothesize that, during DF, genes in the IFN system and complement inhibitor play a role in lowering virus production and reducing tissue damage. In patients with DHF, the dysfunction of immune cells, complement, and cytokines increases viral load and tissue damage. © 2008 by the Infectious Diseases Society of America. All rights reserved.